FURTHER DEVELOPMENT AND EXPANSION OF REMOTE BANKING SERVICES (Conferencea, 2022)
From the first days of the quarantine, all commercial banks focused on further development of remote banking services, improvement of mobile applications, activation of online deposit, credit and payment services and expansion of opportunities to deliver all types of banking services to customers without coming to the bank building.